Ectoparásitos en juveniles deColossoma macropomum “gamitana” y Piaractus brachypomus “paco” cultivados en estanques de tierra, CICMCR - IIAP- San Martín, 2013 - López Marín, Poul Anthony (2021)
The objective of this work was to identify the ectoparasites in juvenile cultures of Colossoma macropomum and Piaractus brachypomus, to determine the parasitic indices, the correlation of the parasite abundance with the weight-length and the limnological parameters of the water, by means of the Spearman correlation coefficient (rs). 80 specimens were collected, (40 per species), from 2 culture ponds, monthly monitoring their limnological parameters of the water. The fish were necropsied, and the samples of the gill arches, skin, fins, nostrils, mouth and eyes were analyzed with a stereoscope and microscope. The prevalence (P), abundance (A), intensity (I), mean intensity (MI), mean abundance (AM) and community status indices were evaluated. In Colossoma macropomum the monogeneans were recorded: Anacanthorus spathulatus, Mymarothecium boegeri, Notozothecium janauachensis and Anacanthorus sp1, the copepod Gamidactylus jaraquensis and the protozoa, Trichodina sp. and Ichthyophthirius multifiliis. In Piaractus brachypomus, the monogeneans, Anacanthorus penilabiatus, Mymarothecium viatorum, Anacanthorus sp2 and the protozoa Trichodina sp. were recorded. and Ichthyophthirius multifiliis. The monogeneans species and the copepod presented high prevalence, abundance and medium intensity, being considered central species. It is concluded that there was no weight-length correlation in the juveniles of Colossoma macropomun and Piaractus brachypomus with the abundance of ectoparasites.